Structural control of Jurassic aquifer geometry in the tabular Middle Atlas Morocco - Mouljebouj, Soukaina; Saadi, Mohamed; Souiri, Smail; Kounti, Imane; moutchou, Wiame El (Edelweiss Applied Science and Technology, 2025)
This study aims to delineate the geometry of the Jurassic carbonate aquifer in the Agouraï region (Tabular Middle Atlas, Morocco) and to understand the structural controls that influence groundwater flow and storage. An integrated approach was adopted, combining remote sensing techniques with subsurface geological data. Tectonic lineaments were extracted from Landsat 8 OLI satellite images using Principal Component Analysis (PCA), directional Sobel filters, and Gram-Schmidt fusion. These results were then correlated with lithological and structural data from hydrogeological borehole logs to build a three-dimensional geometric model of the aquifer. The analysis identified 1,248 lineaments, revealing a structural framework dominated by NE-SW (45%) and E-W (30%) trending fault systems. Drilling data confirmed that these structures act as major drains, creating a series of horsts and grabens. Aquifer thickness varies significantly across these faults, from 78 meters near the Timelouka fault to a maximum of 180 meters in the depocenter of the Agouraï basin. The combined PCA and Sobel method proved most effective, achieving a geological compliance rate of 90.6%. The main limitations of the study are the spatial resolution of satellite imagery (15-30 meters), which may not detect smaller fractures, and the uneven distribution of drilling data. Future research should incorporate high-resolution geophysical surveys to refine the model. The resulting structural map serves as a predictive tool for groundwater exploration, highlighting areas with high potential for future water drilling. This provides a practical guide for the sustainable management of water resources in this semi-arid region. This study is the first in the Agouraï region to quantitatively link remotely detected surface lineaments with the geometry of the subsurface aquifer. Its originality lies in demonstrating that NE-SW trending faults are the main control on aquifer thickness, offering a new hydrogeological framework for the Tabular Middle Atlas.